2015
DOI: 10.1177/1470320315600086
|View full text |Cite
|
Sign up to set email alerts
|

ACE polymorphisms and the acute response of blood pressure to a walk in medicated hypertensive patients

Abstract: Hypothesis/Introduction: Polymorphisms of the angiotensin converting enzyme (ACE) gene can interfere with exercise-induced acute blood pressure (BP) reduction. This cross-over study investigated the acute effect of a single walk on BP and tested whether polymorphisms of the ACE gene might explain the variation in BP responses. Materials and methods: Thirty-four healthy medicated individuals were randomized to one control and one walking session at 60-75% of heart rate reserve. Subjects left the laboratory wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 68 publications
(95 reference statements)
2
18
0
1
Order By: Relevance
“…polymorphism showed higher levels of serum ACE, whereas individuals II homozygous exhibited reduced levels of ACE compared to DD homozygotes (Rigat et al, 1990). In line with Santana et al, (2011), we recently found that hypertensive medicated carriers of the I-allele experienced PEH while DD homozygotes did not (Goessler et al, 2015). Following a single bout of exercise, Santana et al, (2011) observed PEH and increased nitric oxide levels only in carriers of the I allele.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…polymorphism showed higher levels of serum ACE, whereas individuals II homozygous exhibited reduced levels of ACE compared to DD homozygotes (Rigat et al, 1990). In line with Santana et al, (2011), we recently found that hypertensive medicated carriers of the I-allele experienced PEH while DD homozygotes did not (Goessler et al, 2015). Following a single bout of exercise, Santana et al, (2011) observed PEH and increased nitric oxide levels only in carriers of the I allele.…”
Section: Discussionmentioning
confidence: 56%
“…In brief, volunteers were healthy men or women without known cardiovascular or pulmonary disease, age ≥40 years, non-smokers, clinically diagnosed with hypertension according to the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (Chobanian et al, 2003) and being treated for at least 3 months with an angiotensin receptor blocker and/or ACE inhibitor. After screening and signing the informed consent, 34 individuals performed one control session and one exercise session (Goessler et al, 2015). The study was approved by the Research Ethics Committee of the State University of Londrina -Brazil (232/2013).…”
Section: Methods Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gus et al 16 compararam fatores de risco para doenças cardiovasculares no Rio Grande do Sul, em período temporal de 2002 a 2014, e puderam verificar que a prevalência de HAS aumentou a despeito de uma redução na prevalência de sedentarismo. Em verdade, contemporaneamente, alguns olhares da ciência já se propõem a observar pressupostos genéticos, quando da análise entre atividade física e saúde cardiovascular, pormenorizando dessa forma um discurso hegemônico mais grosseiro, que despreza parâmetros que podem estar associados à responsividade individual de cada sujeito ao estímulo do esforço físico 17,18 . É escassa a literatura no que diz respeito à prevalência de HAS em estudantes universitários, porém existem evidências de uma relação inversa entre anos de escolaridade e prevalência de HAS.…”
Section: Classificação Da Pressãounclassified